The Impact of Background Music in Reducing Stress During Preclinical Dental Laboratories - Varma, Sudhir Rama; Thomas, Shibu; Al Radaideh, Ahmed; Ergieg, Suleiman; Fayez, Esraa; Malik, Lubna (Journal of International Society of Preventive & Community Dentistry, 2019)
The reported high level of stress among dental students and its consequences, considering the known benefits of background music (BM). This study was designed to evaluate students' level of stress and impact of BM on their efficiency of work, performance, and learning ability during preclinical laboratory. In this cross-sectional questionnaire study, 61 preclinical students from the College of Dentistry, Ajman university-Fujairah campus who met the defined inclusion criteria participated. After a semester of the normal laboratory without BM, various genres of BM were introduced in the laboratory. Psychological stress assessment was done using the perceived stress scale. Students were asked to fill up a written feedback questionnaire at the end of 6 weeks of BM. Descriptive statistics and Chi-square test were used to study the statistical relationships among groups. About 100% male and female students were found to be highly stressed due to exams and tests, 98% were stressed due to lack of time in the laboratory. About 82.5% females and 76% of males sample population expressed passion for music and also reported BM to be helpful to reduce stress in the preclinical laboratory and also to increase their concentration level. A strong positive relation has been shown in the reduction of stress with the BM in the preclinical laboratory.